2015
DOI: 10.4314/gmj.v49i3.5
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated risk factors of asymptomatic bacteriuria in ante-natal clients in a large teaching hospital in Ghana

Abstract: Introduction: Asymptomatic bacteriuria, the presence of bacteria in urine without symptoms of acute urinary tract infection, predisposes pregnant women to the development of urinary tract infections and pyelonephritis, with an attendant pregnancy related complications. Objective: To measure the prevalence of asymptomatic bacteriuria among antenatal clients at the Korle-Bu Teaching Hospital in Ghana and its' associated risk factors. Methods: A cross-sectional study involving 274 antenatal clients was conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
33
7
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(67 citation statements)
references
References 11 publications
15
33
7
5
Order By: Relevance
“…19 In the present study, insufficient presented a probability of being admitted for a sensitive condition which was 2.40 times higher than for the other variables. The quality of the process of the prenatal care, ascertained from the records of the procedures undertaken during the consultation, such as the clinical approach, physical examination, checking blood pressure, obstetric palpation, auscultation of FHB and assessment of nutritional status, among others, showed this not to be meeting the needs of the pregnant women, revealing a worse prognosis and the occurrence of unnecessary admissions, in the light of other studies undertaken in the States of Espírito Santo and Rio de Janeiro.…”
Section: Discussioncontrasting
confidence: 56%
“…19 In the present study, insufficient presented a probability of being admitted for a sensitive condition which was 2.40 times higher than for the other variables. The quality of the process of the prenatal care, ascertained from the records of the procedures undertaken during the consultation, such as the clinical approach, physical examination, checking blood pressure, obstetric palpation, auscultation of FHB and assessment of nutritional status, among others, showed this not to be meeting the needs of the pregnant women, revealing a worse prognosis and the occurrence of unnecessary admissions, in the light of other studies undertaken in the States of Espírito Santo and Rio de Janeiro.…”
Section: Discussioncontrasting
confidence: 56%
“…This could be imputed to the fact that CoNS and S. aureus are normally encountered in UTIs in the 20-30 year group and more than 64% of our study population came from this group. In Ghana, Gram positive bacteria appears to be conventional in pregnant women presenting with ASB as S. aureus and Enterococcus dominated in similar analysis in the country [23,32] Susceptibility of isolates to gentamicin and amikacin were highest which could possibly be the infrequent prescription of these drugs in the treatment of UTI infections at both hospitals as these drugs are only used in the management of severe and vulnerable cases (Personal communication).…”
Section: Resultsmentioning
confidence: 97%
“…These results agree with Labi et al, in his study in Ghana found that 26.7% of the positive cultures were infected by Enterococcus. 14 Molina et al, reported that E.coli and proteus mirabilis were the most frequent isolated bacteria in positive ASB cases. 17 Anku G et al, reported that most of gram positive organisms were sensitive to teicoplanin, linzolid, and chloramphenicol.…”
Section: Discussionmentioning
confidence: 99%